2008
DOI: 10.1163/156856208783432453
|View full text |Cite
|
Sign up to set email alerts
|

Poly(lactic acid) scaffold fabricated by gelatin particle leaching has good biocompatibility for chondrogenesis

Abstract: Three-dimensional poly(L-lactic acid) (PLLA) scaffolds with high porosity and an average pore size of 280-450 microm were fabricated using gelatin particles as porogen. The particles were bonded together by incubation in saturated water vapor at 70 degrees C for 3.5 h. After casting the PLLA/1,4-dioxane solution, freeze-drying and porogen leaching with 70 degrees C water, a porous scaffold with well-interconnected pores and some nano-fibers was obtained. The biological performance of the scaffold was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…A number of studies that have investigated the use of PLLA in tissue engineering in vivo have reported satisfactory results for bone regeneration 29,30 , guided tissue regeneration 31 , nerve peripheral regeneration 32 , and cartilaginous tissue 33 . PLDLA copolymer is compatible with 34 and suitable for use as a bone graft substitute [35][36][37][38] , meniscus replacement 39,40 , suture cords/threads 41 and axon regeneration 42 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies that have investigated the use of PLLA in tissue engineering in vivo have reported satisfactory results for bone regeneration 29,30 , guided tissue regeneration 31 , nerve peripheral regeneration 32 , and cartilaginous tissue 33 . PLDLA copolymer is compatible with 34 and suitable for use as a bone graft substitute [35][36][37][38] , meniscus replacement 39,40 , suture cords/threads 41 and axon regeneration 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical and biological properties of biomaterials significantly influence chondrogenesis and the long-term maintenance of the structural integrity of the neo-formed tissue. The three-dimensional nature of the scaffolds promotes maintenance of rounded cell morphology and the elevated expression of glycosaminoglycans and type II collagen (Nettles et al, 2002;Gong et al, 2008). Other advantage is that cell delivery supports may act as barrier to the invasion of the graft by fibroblasts, which may otherwise induce fibrous repair (Frenkel et al, 1997).…”
Section: Scaffoldsmentioning
confidence: 99%
“…To overcome this problem, the phase separation techniques are used in combination with other scaffold fabrication techniques such as porogen leaching. The combined technique provides broader control over porous architectures from macro-, micro-to nanoscales (Chen and Ma 2004;Gong et al 2008;Ma et al 2005c;Wei and Ma 2006;Zhou et al 2005). Gong et al (2008;Zhou et al 2005) fabricated well connected PLLA scaffolds via porogen leaching with phase separation technique in which gelatin particles were used as porogens.…”
Section: Phase Separationmentioning
confidence: 99%
“…The biological performance of the scaffold was evaluated by in vitro chondrocyte culture and in vivo implantation. In comparison with the control scaffold fabricated with NaC1 particles as porogen under the same conditions, the experimental scaffold had better biological performance because the gelatin molecules were stably entrapped onto the pore surfaces (Gong et al 2008). Surface modification was also taken place in order to improve the biocompatibility of these PLLA scaffolds.…”
Section: Phase Separationmentioning
confidence: 99%